Industrial Applications of Renewable Biomass Products Past, Present and Future - Goyanes, Silvia Nair.; D'Accorso, Norma Beatriz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book effectively links the latest scientific advances to current technological applications of polymers, mainly focusing on biodegradable polymers obtained from biomass. The individual chapters were written by academic and industry researchers alike, introducing readers to topics that have received little attention in the literature to date. Key topics covered include polymers used in various areas such as food packaging, pharmaceuticals, energy production and the cosmetics industry, as well as the treatment of aqueous effluents. .
Chapter 1. Synthesis and applications of carbohydrate-based polyurethanes -- Part 1. Medical Applications: Chapter 2. Biodegradable polymers for bone tissue engineering -- Chapter 3. Industrial Applications of Renewable Biomass Products - Past, Present and Future -- Chapter 4. Innovative systems from clickable biopolymer-Based hydrogels for drug delivery -- Chapter 5. Applications of glycosaminoglycans in the medical, veterinary, pharmaceutical and cosmetic fields -- Chapter 6. Bacterial Cellulose Nanoribbons: A New Bioengineering Additive for Biomedical and Food Applications -- Part 2. Oil Industry: Chapter 7. Biobased additives in oilwell cement -- Chapter 8. Polymers from biomass widely spread in the Oil industry -- Chapter 9. Modified starches used as additives in Enhanced Oil Recovery (EOR). Part 3. Other Applications Related to Environmental Care: Chapter 10. Chitosan: from organic pollutants to high-value polymeric materials -- Chapter 11. PLA based nanocomposites reinforced with CNC for food packaging applications: from synthesis to biodegradation -- Chapter 12. Removal of Pollutants Using Electrospun Nanofiber Membranes.
Keywords: Polymers; Biomaterials; Sustainability; Green chemistry; Chemistry, Organic; Polymers; Biomaterials; Sustainability; Green Chemistry; Organic Chemistry